Evolución de medios digitales y convencionales - Mora Magallanes, Melissa Anabell (2022)
This research work seeks to analyze the evolution of conventional media towards digital environments and the challenges they face to capture new audiences. For its effect, news content exposed in the Tik Tok social network of two traditional media has been observed: El Comercio, as the original print media; and Ecuavisa, television medium; both cross-platform today. A clear search for youth audiences has been detected through different resources, but also a marked difference between the audiences: centennials and millennials. To identify the level of capture of these audiences, it was necessary to measure the influence of the news content of El Comercio and Ecuavisa exposed on the TikTok platform on their followers, which, at first glance, denotes little interaction but through observation sheets, Interviews and surveys applied to 32 students of the University of Guayaquil of the Faculty of Social Communication, the survey was applied because being of ages corresponding to the centennial and millennial generation, they justify the contents that the media Ecuavisa and newspaper El Comercio publish in their social networks.............